Analisis Kebutuhan Pengembangan Perkuliahan Getaran dan Gelombang untuk Meningkatkan Kemampuan Penalaran Ilmiah Calon Guru Fisika - Dwi Fajar Saputri; Nurhayati; Lukman Hakim Alsaggaf; Wahyudi; Adi Pramuda (Postgraduate, University of Mataram, 2025)
This study aims to analyze the development needs of the Vibrations and Waves course to facilitate the development of scientific reasoning skills in prospective physics teachers. A mixed-methods approach with a convergent design was used. A parallel approach was used to obtain a comprehensive overview of lecture implementation, students’ and lecturers’ perceptions, and student scientific reasoning profiles. Participants consisted of 37 students and three lecturers. Data were collected through document analysis, interviews, and a scientific reasoning test adapted from the Lawson Classroom Test of Scientific Reasoning (LCTSR), and a questionnaire. The results of the study indicate that learning outcomes have included elements of concept mastery, problem-solving, and scientific reasoning, but the implementation of learning is still expository, practicums tend to be verification-based, and assessments focus on mathematical calculations. The LCTSR score indicates that students' scientific reasoning abilities are in the very low to low category in almost all aspects, especially proportional reasoning, variable control, probabilistic reasoning, and hypothetico-deductive reasoning. Students and lecturers assessed the need for the implementation of inquiry-based learning strategies, problem-based learning, and project-based learning to optimize the development of scientific reasoning. This study recommends that there is a need to develop Vibrations and Waves lecture tools that explicitly target strengthening scientific reasoning through systematic and planned teaching strategies that encourage students to reason and think deeply, such as inquiry-based learning models, problem-based learning, and project-based learning.